Peran Ketangguhan dan Dukungan Sosial Keluarga terhadap Stres Akademik pada Mahasiswa yang sedang Menyusun Skripsi - Yumika, Tasya; Marheni, Adijanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
Academic stress is a variety of stresses faced by students in connection with study and lecture. Academic stress in students who are undergoing dissertation occurs because students are required to be independent in completing academic tasks. Academic stress will have a negative impact on physical, psychological and academic performance. The high and low levels of academic stress are influenced by the presence of hardiness within the individual, as well as the social support of the family. This research is using a quantitative-research to know the role of hardiness and social support of the family against academic stress in students who are drawing up a thesis at Udayana University. Sampling is done using the cluster random sampling technique. A total of 108 students from Udayana University who are drafting the thesis are used as subjects in this study. The measurement tools used are the academic stress scale, the hardiness scale, and the family’s social support scale. The result of the multiple linear regression test showed a regression coefficient value of 0.676, a determination cofficient of 0.642, a significance value of 0.000 (p<0,05), which means that hardiness and social support jointly play a signative role against the academic stress of students who are drafting the thesis. Furthermore, the value of the beta coefficient is standardized on the hardiness variable of -0.286 and family social support is -0.114. The results showed that hardiness variables played a greater role in lowering student academic stress levels compared to family social support variables.